Procedure for determining the remaining time to initiation of chloride induced reinforcement corrosion for existing concrete structures - Polder Rob B.; Boutz Michel; Ottelé Marc (MATEC Web of Conferences, 2022)
For efficient asset management of reinforced concrete infrastructure, owners want to know when to expect corrosion in structures. At present, no widely accepted procedures for testing of existing structures for the remaining time to corrosion initiation are available. This paper describes such a procedure, based on the authors’ long-time experience. From about 20 years age, the concrete contains its mature response to actual environmental loads, e.g. chloride ingress. By measuring the mean and standard deviation of the actual cover depth, taking chloride profiles, assuming a few parameters and a simple, pragmatic model, the expected time to corrosion initiation for a particular test area can be predicted. Required numbers of cores and samples per core are given. Uncertainties are taken into account by subtracting a safety margin from the measured concrete cover depth. Results of six cores per test area are classified and interpretations are given. Because of large variability, the results are classified in three ranges of time to corrosion initiation: five years or less, five to fifteen years, or more than 15 years. The procedure has been approved by the relevant national Standards committees and was issued as a CUR Recommendation in 2018. It is illustrated based on a field case and the obtained results are discussed.